EXISTENTIAL NATURE OF THE PHILOSOPHY OF VASYL STUS AND ALBERT CAMUS - Kotets, Yana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The article considers the specifics of the existential nature of the poet-thinker Vasyl Stus’ philosophy. Aspects of Vasyl Stus’ work that illuminate the concept of man and being in the context of existentialist philosophy are described. The philosophy of V. Stus and A. Camus’ existentialism is analyzed and common motives of conformity in understanding the self-worth and uniqueness of man and being are established. The concept of rebellion, as a positive expression of the absurd from the thinker’s position, is singled out. The aim and tasks: to characterize the main aspects of Vasyl Stus’ philosophizing with further comparative analysis with the philosophy of Albert Camus. In particular, it is intended to highlight commonalities and differences. Research methods. The study uses a synthesis of the following scientific methods: biographical (the reference to fragments of the writer’s biography for interpretation of his work with elements of psychological analysis); comparative (typological identification and analysis of typological rises not caused by direct contacts). Research results. The philosophizing of V. Stus and A. Camus and their differences are analyzed. The Ukrainian philosopher V. Stus and the French philosopher A. Camus had much in common in their views, namely, that both claimed to be unique and doomed to human loneliness in the world. Also, thinkers were convinced of the absurdity of human existence. Thinkers believed that it was worth accepting the absurdity of life. It is characteristic of the poetry of Stus’ and Camus’ lack of trust in the outside world. Life is a constant borderline situation. Philosophers opposed totalitarian societies and restrictions on democratic human freedoms. Discussion. Comparing the specifics of the philosophical views of the Ukrainian poet-philosopher Stus and the French Albert Camus, it should be noted that both are existentialists with similar views. Conclusion. Analyzing the two artists and relying on the work of M. Kotsyubynska, E. Sverstyuk, I. Malenky, N. Zborovska, and other researchers, it can be argued that their views intersect in the categories of sense of life and absurdity, as well as in understanding certain moral and ethical principles. Apparently, the only significant difference is that A. Camus was a man of atheistic views, and V. Stus, as research intended, was a religious man. Both artists were against totalitarian societies and restrictions on democratic human freedoms. For the Ukrainian and French philosophers, freedom is the basis of all moral and ethical values.